Characteristics of He Ion Implanted Layers on Single‐Crystal Diamond. Issue 22 (27th September 2018) - Valentin, Audrey; De Feudis, Mary; Brinza, Ovidiu; Tardieu, André; William, Ludovic; Tallaire, Alexandre; Achard, Jocelyn
Abstract : Ohmic contact formation on lightly doped or intrinsic diamond is highly desirable particularly for detection application. Nevertheless, good quality of such contacts is difficult to obtain and the production of a thin graphitic layer underneath diamond surface can be an interesting approach. In this paper, intrinsic freestanding single‐crystal CVD samples are implanted with 10 keV He ions at different fluences. Simulations are performed to show that the used fluences are high enough to ensure the creation of an amorphous layer. The implanted layers are characterized before and after annealing by a combination of photoluminescence imaging, confocal microscopy, transmission electron microscopy (TEM), resistivity measurements, and Raman spectroscopy. After annealing, the layer resistivity and the layer density decrease. The values measured after annealing are close to the values measured on graphite. Raman spectroscopy results show that the implantation leads to the creation of a highly disordered graphite layer which quality improves after annealing to reach that of nanocrystalline graphite. It also shows that the use of light ions at relatively low energy makes possible the formation of this graphitic layer at the surface of the sample. These promising results pave the way for ohmic contact fabrication on lightly doped diamond. Abstract : Conductive layers are created in intrinsic freestanding single‐crystal CVD diamond layers by He ion implantation. The implanted layers are characterized before and after annealing by a combination of photoluminescence imaging, confocal microscopy, transmission electron microscopy (TEM), resistivity measurements, and Raman spectroscopy. After annealing, the conductive layer characteristics are close to the characteristics of nanocrystalline graphite.